STUDY ON THE CORRELATIONS BETWEEN CHAKRA SYSTEM AND AYURVEDIC MEDICINE (International Journal of Ayurveda and Pharma Research, 2020)
When we mention about “Chakra, Nadis, or Channels”, many of us, especially scholars may think that they are related to the theory of Ayurvedic medicine. In fact, they are all basic concepts of Yoga. Both Ayurveda and Yoga are also important branches of the traditional Indian medicine but the objectives of both of them are different. The former is a medical science to promote physical well-being. The later is a religious system to target on spiritual growth, enlightenment and liberation. Therefore, this paper aims to provide a clear explanation on correlations between Chakra System and Ayurvedic medicine. Firstly, the relationship between Chakra system versus Ayurvedic medicine is argued based on a direct discourse on the source of Chakra System. Next, based on indirect discourse on the 2 major works in Ayurvedic medicine, there is no elaboration on the Chakra System. Hence, we can further prove and conclude that Chakra System is not a concept of Ayurvedic medicine where both of them are not related to each other. Finally, we urge to other scholars to pay attention to this matter that do not mix up these two different concepts to continue implanting the incorrect concept to the rest of the professionals.